2019
DOI: 10.1038/s41419-019-1378-7
|View full text |Cite
|
Sign up to set email alerts
|

p53 induces senescence through Lamin A/C stabilization-mediated nuclear deformation

Abstract: p53-mediated cellular senescence has been intensively investigated, because it is important for tumor suppressive function. In addition, p16/INK4A is well known to be critical for cellular senescence. However, detailed molecular mechanism or relevance between p53 and p16-mediated senescence has not been demonstrated yet. Here we show that p53 induces p16 through Lamin A/C stabilization via direct interaction. Stabilized Lamin A/C promotes degradation of BMI-1 and MEL-18 (Polycomb repressor complex 1, PRC1), wh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
19
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(26 citation statements)
references
References 44 publications
0
19
0
Order By: Relevance
“…, 2017 ). Interestingly, another study has recently demonstrated that overexpression or activation of p53 induces nuclear deformation reminiscent of the irregular nuclear shapes found in HGPS cells and induces cellular senescence ( Yoon et al. , 2019 ).…”
Section: Discussionmentioning
confidence: 99%
“…, 2017 ). Interestingly, another study has recently demonstrated that overexpression or activation of p53 induces nuclear deformation reminiscent of the irregular nuclear shapes found in HGPS cells and induces cellular senescence ( Yoon et al. , 2019 ).…”
Section: Discussionmentioning
confidence: 99%
“…In recent decades, lamin mechanical stability [13]. Nevertheless, recent studies suggest that they also play a vital role in crucial cellular processes, such as replication of DNA, tumorigenesis, progression of cell cycle, mitotic spindle formation, aging, differentiation of adult stem cell, and chromatin organization [10,[14][15][16]. Studies on the lamins family have long focused on type A lamins, but few have focused on type B lamins, especially lamin B1.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, wild-type p53 stabilizes lamin A/C via direct interaction, and the stabilized lamin A/C with p53 binding (increased expression of lamin A/C) was associated with nuclear deformation [10]. These findings also support that p53 plays an important role in chromatin condensation, nuclear shrinkage and deformity by facilitating degradation of nuclear lamins [38,39], and induction of nuclear deformity by stabilizing lamin A/C which should be removed [10]. Therefore, the restoration or enhancement of p53 gene could be a good strategy for the treatment of pKAL in cancer patients who are not eligible for the conventional therapies due to the patient's poor condition.…”
Section: Discussionmentioning
confidence: 99%
“…Proteolysis of Lamins is associated with collapsed nuclei and chromatin condensation in p53-dependent apoptosis [38]. Moreover, wild-type p53 stabilizes lamin A/C via direct interaction, and the stabilized lamin A/C with p53 binding (increased expression of lamin A/C) was associated with nuclear deformation [10]. These findings also support that p53 plays an important role in chromatin condensation, nuclear shrinkage and deformity by facilitating degradation of nuclear lamins [38,39], and induction of nuclear deformity by stabilizing lamin A/C which should be removed [10].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation